Being la Dominicana : race and identity in the visual culture of Santo Domingo - Quinn, Rachel Afi (Urbana : University of Illinois Press, 2021)
"This book investigates the ways Dominican visual culture portrays Dominican women and how women represent themselves in their own creative endeavors in response to existing stereotypes. Delving into the dynamic realities and uniquely racialized gendered experiences of women in Santo Domingo, Quinn reveals the way racial ambiguity and color hierarchy work to shape experiences of identity and subjectivity in the Dominican Republic. She merges analyses of context and interviews with young Dominican women to offer rare insights into a Caribbean society in which the tourist industry and popular media reward, and rely upon, the ability of Dominican women to transform themselves to perform gender, race, and class"--
Fictions of Identity in Trópico de Sangre -- Queering Minerva -- Color and Its Consequences -- Albania and Inez: "Niña No Esposa" -- Girlhood Interrupted -- #TodosSomosEmely -- The Art of Rage -- Curiouser and Curiouser -- Notes -- Introduction -- Chapter 1. Sites of Identity -- Chapter 2. Me Quedo con la Greña -- Chapter 3. Whiteness, Transformative Bodies, and the Queer Dominicanidad of Rita Indiana -- Chapter 4. A Thorn in Her Foot -- Chapter 5. The Camera Obscura -- Chapter 6. Feminist Rage and the Right to Life for Women in the Dominican Republic -- Works Cited -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
JSTOR
Keywords: Women -- Dominican Republic; Feminism -- Dominican Republic; Dominicans (Dominican Republic) -- Race identity; Femmes -- République dominicaine; Féminisme -- République dominicaine; Dominicains (Peuple) -- Identité ethnique; SOCIAL SCIENCE / General; Feminism; Women; Dominican Republic